Structural transformation of vanadate nanotubes into vanadate oxides nanostructures during the dry reforming of methane - Oton, Lais F. (2019)
The metal-containing vanadate nanotubes namely MeVO-NT (Me=Ni, Co or Pt) were in situ transformed into vanadate oxides nanostructures i.e., MeVxOy, during the methane dry reforming. All the experimental observations through Raman, HRTEM, XRD, XPS, SEM-EDS, TG-FTIR and elemental analysis, strongly suggested that the VOx (MeV2O7, V2O5 and VO2) support contained the metal species that were involved in the dry reforming of methane (DRM) reaction. The pristine VO-NT catalyst exhibited a fairly low activity in DRM due to its degradation. In the case of CoVO-NT, the Co3O4/VO2, Co3O4/Co2V2O7 and Co3O4/V2O5 phases were deactivated by oxidation of the Co particles, instead of being deactivated by sintering and coking, as well. In contrast to CoVO-NT, PtVO-NT having PtOx/V2O5, PtOx/VO2 or even PtOx/V2O7 phases inhibited heavy carbonaceous deposition on surface, but sintering was not avoided. The NiVO-NT was active due to the stability of the Ni°/Ni2V2O7 active phase in hindering heavy whisker and filamentous carbonaceous deposits on such catalyst. Using Halgren-Lipscomb algorithm in the frame of density functional theory (DFT), transition states energy for all three catalysts were obtained. It was found that PtVO-NT energy profile was lower than CoVO-NT and NiVO-NT counterparts. This suggested that the Pt sites dispersed on VOx structure was catalytic active during the methane activation in DRM whereas the CoVO-NT and CoVO-NT solids were prone to perform side reactions.